Thermochemical Liquefaction of Kraft Lignin As A Waste Management Process - Bob Soile; Moses Akiibinu,Felix Oyeyiola (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
Waste management is the collection, transportation, processing or disposal, monitoring, and managing of waste materials. It tries to reduce the harmful environmental impact of each through different methods, which include but not limited to landfill, incineration, recycling, biological processing, and reduction methods. Generation, utilization and disposal of waste is increasingly becoming a significant problem in many cities of the world, with an exploding world population estimated to have a global doubling time now less than twenty years. This research focuses on energy recovery as a viable method of disposal of non-hazardous biomass components of municipal solid waste with a prototype waste kraft lignin material using the thermochemical liquefaction process. The process used high pressure, high temperature in the presence of kraft lignin, slurry solvent, and a suitable catalyst to produce a mixture of gases, liquid, and solid capable of been used as fuels and chemicals and providing an alternative to the other methods. This value-adding process serves a dual purpose of providing a source of energy and providing an alternative waste management method.